Russia and the Arabs : behind the scenes in the Middle East from the Cold War to the present - Primakov, E. M. (Evgeniĭ Maksimovich) (Basic Books, 2009)
"In Russia and the Arabs, Americans are given a look at Cold War and now post-Cold War relationships in the Middle East through the eyes and roles of Yevgeny Primakov - Russia's Kissinger in every sense of that name. '[The Middle East] is a region I have followed for half a century as a journalist, academic and politician - as a correspondent for Pravda; as deputy director (and later director) of the Institute of World Economy and International Relations at the USSR Academy of Science; at the Academy's Institute of Oriental Studies; as head of the SVR (Russia's foreign intelligence service); as Russian foreign minister, as Russian prime minister and as a deputy in the Duma, Russia's parliament.' Russia and the Arabs is as much a history of the Middle East as a memoir, when Primakov recounts his and the Soviet/Russian roles in the Arab world. He begins with Nasser's Egypt of the early 1950s, and the period in which the USSR gained its first toehold in the Middle East. Primakov emphasizes that despite Arab nationalism - regional identities and politics always trumped pan-Arab ones - and professed revolutionary, even socialist aims, the new regimes sought accommodation with the U.S. and kept their new ally, and primary source of weapons, the USSR at some distance. After Egypt, Primakov turns to examine Lebanon from the Civil War of 1975 to 2005 and the Hariri assassination, to the emergence of Arafat as Palestinian leader, and then to an appraisal of the USSR's overall relationship with and qualified support for Israel - there are now some one million recent Russian emigrants there. In the final chapters, Primakov narrates Russia's frustrated ties with Saddam Hussein, and judges Saddam Hussein to have suffered self-delusion in misreading the U.S., his new supporter during the Iran-Iraq war. This is especially interesting, not the least that Primakov was Putin's envoy to Iraq. Here, too, there is suggestion of Primakov's conspiratorial view of events. The Kurds, Israeli nuclear capabilities, and the future of the Middle East including the consequences of the Iraq War, Iran's growing power and nuclear potential, Hamas, Lebanon and religious divisions are all analyzed in the end."--Review by Gene R. Garthwaite in http://www.historybookclub.com